Visual Content Assignment and Future Teaching Skills: Pre-Service Teachers Perceptions - Balqis Meisya Ghaisani Arifanya; Putu Dian Danayanti Degeng (Riviera Publishing, 2026)
The integration of digital technology in English as a Foreign Language (EFL) education has transformed teaching practices by encouraging the use of visual and multimodal learning materials. Visual content creation assignments have been recognized as potential learning activities that enhance students’ engagement, digital competence, and understanding; however, limited studies have explored how pre-service teachers perceive these tasks as part of their professional preparation. This study aimed to investigate pre-service English teachers’ perceptions of visual content creation assignments, particularly regarding learning engagement, teaching preparation, and understanding of meaning. This research employed a descriptive quantitative approach involving 85 students from the English Language Education Program at Universitas Brawijaya. Data were collected through a 13-item Likert-scale questionnaire distributed via Google Forms and analyzed using descriptive statistics, including mean scores, frequencies, percentages, and standard deviations. The findings revealed that participants demonstrated highly positive perceptions across all measured dimensions. Visual content creation assignments increased students’ motivation and engagement in English learning, strengthened their confidence in utilizing digital media for teaching, and supported their ability to connect English learning materials with real-world contexts. The results indicated that visual content creation tasks functioned not only as learning activities but also as meaningful experiences for developing future teachers’ digital and pedagogical competencies. Therefore, integrating visual content creation assignments into EFL teacher education programs is recommended to support the development of digitally competent and innovative teachers.